Endocytosis and Organelle Targeting of Nanomedicines in Cancer Therapy - Wang, Xiaowei (Int J Nanomedicine, 2020)
Nanomedicines (NMs) have played an increasing role in cancer therapy as carriers to efficiently deliver therapeutics into tumor cells. For this application, the uptake of NMs by tumor cells is usually a prerequisite to deliver the cargo to intracellular locations, which mainly relies on endocytosis. NMs can enter cells through a variety of endocytosis pathways. Different endocytosis pathways exhibit different intracellular trafficking routes and diverse subcellular localizations. Therefore, a comprehensive understanding of endocytosis mechanisms is necessary for increasing cellular entry efficiency and to trace the fate of NMs after internalization. This review focuses on endocytosis pathways of NMs in tumor cells, mainly including clathrin- and caveolae-mediated endocytosis pathways, involving effector molecules, expression difference of those molecules between normal and tumor cells, as well as the intracellular trafficking route of corresponding endocytosis vesicles. Then, the latest strategies for NMs to actively employ endocytosis are described, including improving tumor cellular uptake of NMs by receptor-mediated endocytosis, transporter-mediated endocytosis and enabling drug activity by changing intracellular routes. Finally, active targeting strategies towards intracellular organelles are also mentioned. This review will be helpful not only in explicating endocytosis and the trafficking process of NMs and elucidating anti-tumor mechanisms inside the cell but also in rendering new ideas for the design of highly efﬁcacious and cancer-targeted NMs.